A band notch UWB bandpass filter using dual-stub-loaded multimode resonator with embedded spiral resonator. Issue 2 (April 2014) - Sarkar, Pankaj; Rakshit, Ishita; Adhikari, Sharmili; Pal, Manimala; Ghatak, Rowdra
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents a band-notched ultra-wideband bandpass filter by loading a short stub and an asymmetric step impedance stub in a uniform impedance resonator. The passband extends from 3.04 to 10.8 GHz frequency. The multimode resonator provides a sharp band edge with measured transmission zeros at 2.59 and 13 GHz. The later one is due to source load coupling. The passband insertion loss is within 1.5 dB. The embedded spiral resonator introduces a notch at 5.25 GHz with attenuation of 15 dB. The filter exhibits a wide stop band till 15 GHz. The in band and out of band performance obtained from full-wave electromagnetic simulation and measurement are in close agreement.